Managing Soil Organic Carbon: A Farm Perspective. (August 2014) - Ingram, Julie; Mills, Jane; Frelih‐Larsen, Ana; Davis, McKenna; Merante, Paulo; Ringrose, Sian; Molnar, Andras; Sánchez, Berta; Ghaley, Bhim Bahadur; Karaczun, Zbigniew; Ferrise, Roberto; Dibari, Camilla; et al.
Summary Farming practices that lead to declining returns and inputs of carbon to soils pose a threat to key soil functions. The EU FP7 interdisciplinary project SmartSOIL is using scientific testing and modeling to identify management practices that can optimise soil carbon storage and crop productivity. A consultation with advisors and policymakers in six European case study regions seeks to identify barriers to, and incentives for, uptake of such practices. Results from preliminary interviews are reported. Overall advisor and farmer awareness of management practices specifically directed towards soil carbon is low. Most production‐related decisions are taken in the short term, but managing soil carbon needs a long‐term approach. Key barriers to uptake of practices include: perceived scientific uncertainty about the efficacy of practices; lack of real life 'best practice' examples to show farmers; difficulty in demonstrating the positive effects of soil carbon management practices and economic benefits over a long time scale; and advisors being unable to provide suitable advice due to inadequate information or training. Most farmers are unconvinced of the economic benefits of practices for managing soil carbon. Incentives are therefore needed, either as subsidies or as evidence of the cost effectiveness of practices. All new measures and advice should be integrated into existing programmes to avoid a fragmented policy approach.